A new species of planthopper in the genus Anotia Kirby (Hemiptera: Auchenorrhyncha: Derbidae) from coconut palm in Costa Rica - Barrantes, Edwin A.; Echavarria, Marco A. Zumbado; Bartlett, Charles R.; Helmick, Ericka E.; Cummins, Paige; Ascunce, Marina S.; Bahder, Brian W. (Zootaxa, 2020)
An ongoing survey for planthoppers associated with palms in the Caribbean basin is being conducted with current efforts on the Caribbean lowlands of Costa Rica. In an expedition in June of 2019, a derbid was found on coconut palms in Alajuela province and was determined to be a new species belonging to the genus Anotia. The novel taxon is described and named Anotia firebugia Bahder & Bartlett sp. n. Additionally, molecular barcode data (COI) is provided for the newly described taxon.